Community-Based Disaster Risk Management Mount Batur Guide Forum In Batur Unesco Global Geopark - Ida Bagus Oka Agastya; Eko Teguh Paripurno (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
In total 24 eruptions took place on Mount Batur, the most recent one occurred in 2000. As one of the geosites in the Batur UNESCO Global geopark, Kintamani District, Bangli Regency, Mount Batur is often used as a tourism destination, where daily trekking activities could involve 500 people before the coronavirus pandemic. However, disaster mitigation facilities such as volcanic hazard information boards and evacuation routes remain limited, making this situation potentially and increasingly vulnerable if Batur Volcano erupts again. To answer the problem of disaster risk management, especially through community participation, in the Mount Batur Area, a community-based disaster risk assessment research is conducted. The research method used is a qualitative method that consists of observation, documentation, and interviews. The selection of informants was carried out purposefully to conduct in-depth interviews according to the issues raised, namely community-based disaster risk management in the Batur UNESCO Global Geopark area. From the research conducted regarding community-based disaster risk reduction in the Mount Batur Trekking Guide Forum (FP2GB) community, several interesting results were obtained, both from tourists and guides. By carrying out CBDRM activities with the guide community, a formulation was obtained in the form of a Standard Operating Procedure (SOP) for trekking Mount Batur which later can be used as a reference for guides and tourists to provide good services as well as community-based, participatory disaster risk management methods.